Ріггінг 3D-моделі автомобіля та його анімація в blender - М’ячиков, І. В.; Клепіков, К. В. (ХНУРЕ, 2025)
Тhis paper describes the concept of rigging in 3D graphics and its role in simplifying the animation process. Rigging is the process of creating a skeletal structure for 3D models, allowing them to move realistically. The key components of rigging, including bones, controllers, skinning, and inverse and forward kinematics, are analyzed in detail. Special attention is given to the application of rigging in character animation and mechanical objects, such as vehicles. Properly configured rigging enhances the realism of animations and simplifies the work of animators. The study highlights the role of rigging in modern industries, including game development, filmmaking, and advertising.
Keywords: 3D-модель автомобіля; анімація